ANALISIS PENGARUH PEMASARAN MEDIA SOSIAL DAN CELEBRITY ENDORSER TERHADAP ELECTRONIC WORD OF MOUTH ENGAGEMENT PADA MINAT BELI (Studi. pada Kosmetik Wardah di Semarang) - Monicha, Desy; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2019)
The purpose of this study to analyze social media marketing, celebrity endorser on electronic word of mouth engagement and the impact on purchase intention. Using social media marketing strategies and celebrity endorsers, Wardah hopes that they can influence electronic word of mouth engagement so that Wardah's product sales can increase and can be ranked first in the Top Brand Award in various products.The population of the study was all consumers who had ever done purchase or ever to use Wardah cosmetics, where respondents are Semarang people. The samples in this study were 120 respondents. The method of collecting data through questionnaires via online with purposive sampling method. The provisions are that respondents who have bought ore are using Wardah products, know one of the endorsers and know the Wardah Instagram in Semarang City. This study uses analytical techniques of Structural Equation Modeling (SEM) with AMOS 24.0 as the analysis instrument. The result show that the social media marketing has a positive and significant effect on electronic word of mouth engagement, celebrity endorser has a positive and significant effect on electronic word of mouth engagement, electronic word of mouth engagement has a positive and significant effect on purchase intention.